The Experience of Nurses in the Implementation of discharge planning for post-stroke - Dwi Intan Pakuwita AR; Asti Melani Astari; Dina Dewi Sartika Lestari Ismail (Universitas Aisyah Pringsewu, 2022)
The Implementation of discharge planning (DP) for stroke patients is very important because of the phenomenon that stroke can cause disability and last for a long time. This study describes the outcome with proper treatment of post-stroke disability can be minimized. The data analyzed in this study is the relationship between family knowledge about stroke to the family readiness in accepting of housing stroke sufferers. The result is there is a significant relationship between family knowledge about stroke and family readiness in accepting of stroke sufferers. So it is important to do for preparing the family readiness by supporting the knowledge on about the next post stroke patient care at home. This study uses a qualitative method by a phenomenological approach through in-depth interviews to 10 nurses in the Stroke Unit. The results of this study through data analysis, obtain 14 themes. Of these fourteen themes, two core themes were obtain discharge planning is the duty and responsibility of nurses and discharge planning helps simplify the treatment process.